Hierarchical Self-assembly of Well-Defined Louver-Like P-Doped Carbon Nitride Nanowire Arrays with Highly Efficient Hydrogen Evolution - Li, Bo; Si, Yuan; Fang, Qian; Shi, Ying; Huang, Wei‑Qing; Hu, Wangyu; Pan, Anlian; Fan, Xiaoxing; Huang, Gui‑Fang (Nano-Micro Letters, 2020)
Self-assembled nanostructure arrays integrating the advantages of the intrinsic characters of nanostructure as well as the array stability are appealing in advanced materials. However, the precise bottom-up synthesis of nanostructure arrays without templates or substrates is quite challenging because of the general occurrence of homogeneous nucleation and the difficult manipulation of noncovalent interactions. Herein, we first report the precisely manipulated synthesis of well-defined louver-like P-doped carbon nitride nanowire arrays (L-PCN) via a supramolecular self-assembly method by regulating the noncovalent interactions through hydrogen bond. With this strategy, CN nanowires align in the outer frame with the separation and spatial location achieving ultrastability and outstanding photoelectricity properties. Significantly, this self-assembly L-PCN exhibits a superior visible light-driven hydrogen evolution activity of 1872.9 μmol h−1 g−1, rendering a ~ 25.6-fold enhancement compared to bulk CN, and high photostability. Moreover, an apparent quantum efficiency of 6.93% is achieved for hydrogen evolution at 420 ± 15 nm. The experimental results and first-principles calculations demonstrate that the remarkable enhancement of photocatalytic activity of L-PCN can be attributed to the synergetic effect of structural topology and dopant. These findings suggest that we are able to design particular hierarchical nanostructures with desirable performance using hydrogen-bond engineering. Highlights: 1 The self-assembled louver-like P-doped carbon nitride (L-PCN) nanowires is firstly constructed. 2 L-PCN nanowires show efficient charge transport, as demonstrated by experimental and theoretical approach. 3 L-PCN nanowires exhibit significantly boosted HER activity of 1,872.9 μmol h−1 g−1 (λ > 420 nm).